Peran Manajemen Sumber Daya Manusia dalam Meningkatkan Daya Saing UMKM di Era Digital - Mohd Pajri (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
This research reveals that effective Human Resource Management (HRM) is essential to improve the competitiveness of MSMEs. In this research that uses descriptive qualitative methods, researchers review how improving the competence and quality of HRM through continuous training and development can help MSMEs adapt to market changes and improve their performance. The result of this study is how good HR Management not only improves the quality of the workforce, but also contributes to the sustainability and competitiveness of MSMEs in an increasingly competitive market. So that by optimising HR management, MSMEs can create a positive work environment, which in turn increases employee motivation and productivity.